Successful treatment of intractable neuralgia in patients with typical and atypical Ramsay Hunt syndrome by transcutaneous facial nerve stimulation: a case series study - Deng, Yan-Bo; Zhong, Ying; Lin, Yu-Xian; Lin, Chen; Ji, Pin-Pin; Wang, Shen-Yin; Gong, Wei-Yi (Frontiers in Neuroscience, 2025)
ObjectiveTypical Ramsay Hunt syndrome (RHS) is a rare peripheral facial neuropathy associated with reactivation of latent varicella-zoster virus in the geniculate ganglion. Atypical RHS is characterized by the involvement of multiple cranial nerves and cervical roots, leading to more complex manifestations. The primary goal of treatment is to reduce the occurrence of late complications, especially in patients with devastating postherpetic neuralgia (PHN). To date, there is no definitive effective treatment. We present a case series of patients with typical and atypical RHS and severe PHN, who were successfully treated with transcutaneous facial nerve stimulation (FNS).Materials and methodsThis is a retrospective case series including two atypical RHS cases and one typical RHS case. The first patient with atypical RHS suffered from persistent otalgia with severe paroxysmal radiation to the dermatome of fifth cranial nerve (CN V) and IX lesion. The second atypical RHS patient with CN V and VII lesions had persistent frontotemporal neuralgia and otalgia, with severe paroxysmal radiation to the CN V and IX dermatome. The third typical patient had persistent otalgia with severe paroxysmal exacerbations. An FNS in the stylomastoid foramen was successfully performed under ultrasound guidance in combination with DSA. Pain assessment was performed during treatment and follow-up, including the type of pain (persistent pain, breakthrough pain, and tactile allodynia) and pain distribution. Pain intensity was assessed using the Number Rate Scale (NRS) and the Verbal Rating Scale (VRS). The therapeutic effect was assessed using the Pain Relief Scale (PRS). In addition, the Pain Relief Ratio (PRR) was calculated as (NRSPre-T - NRSPost-T)/NRSPre-T × 100%, and the treatment was considered effective if the PRR was greater than 50%.ResultsThe t-FNS showed excellent pain relief, particularly for breakthrough pain. The breakthrough pain completely ceased before the FNS was turned off, and the persistent pain decreased from moderate to mild intensity before the patients were discharged. The mild persistent pain of the first patient on the 3-month follow-up and the third patient on the 2-month follow-up had completely disappeared, but the mild persistent pain of the second patient was still felt in the temporal region for 1 year.ConclusionFor the first time, transcutaneous FNS was successfully used to treat intractable PHN in patients with typical and atypical RHS. However, further research is needed to determine the optimal procedure and specific stimulation parameters.